Influence of the use of new technologies in medical semiology education. Systematic review. - Betancourt Masri, Lucas; Bello Astorga, Winston; Osses Alvarado, Ignacia; Sánchez Muñoz, Camila; Ureta Donoso, Sofía; Villaseca Paredes, Vicente; Riquelme, Camila; Herrera Alcaíno, Álvaro (Spanish Journal of Medical Education, 2024)
Introduction: The digital age has influenced the educational landscape by providing tools that enhance both learning and teaching. These technologies enhance the teaching of medical semiotics by offering detailed simulations and interactive visualizations of medical conditions, and by enabling virtual clinical practices that are fundamental to medical education. Objective: To explore the impact of emerging technologies on the teaching of semiotics within medical schools worldwide. Materials and Methods: Systematic review of the literature using the PRISMA protocol in the Web Of Science and SCOPUS databases. Peer-reviewed articles published between 2020-2024, in Spanish and English, were considered. A review and synthesis of the findings were conducted based on inclusion and exclusion criteria. Results: Thirteen articles were reviewed and synthesized, which were divided into three categories: i) Improvement in Academic Performance and Clinical Skills; ii) Student Satisfaction, Motivation, and Engagement; and iii) Impact on Learning Continuity and Flexibility. The categories "Improvement in Academic Performance and Clinical Skills" and "Impact on Learning Continuity and Flexibility" were identified as the most significant, with findings indicating positive influences in both areas, such as a notable increase in theoretical knowledge acquisition and an enhanced positive perception of the pedagogical utility and realism of the technological tools used. Conclusion: The use of technologies shows a promising and positive influence on the teaching-learning process of medical semiotics.